Analysis of Physical Education in Primary Schools - Lestari, Wahyu Adinda Wardani (Jurnal Pendidikan, Kesehatan dan Olahraga, 2024)
Physical education learning is designed to be activity-based and related to a range of types of physical movement/exercise and health maintenance efforts that are appropriate for learners. These activities are designed so that learners become accustomed to doing physical movement and exercise and enjoy doing it because they feel the need to do it and are aware of the importance of maintaining physical health both through physical movement and exercise and by paying attention to the health factors that affect it. This research is a library research and documentation study. The type of research used was qualitative. This research aims to find out the material content of physical education, sport and health teaching materials in SD / MI from grade 1 to grade 6. PJOK material consists of physical education, games and sports and health material